2020
DOI: 10.1177/1747021820979518
|View full text |Cite
|
Sign up to set email alerts
|

Time perception in human movement: Effects of speed and agency on duration estimation

Abstract: While the effects of synthesised visual stimuli on time perception processes are well documented, very little research on time estimation in human movement stimuli exists. This study investigated the effects of movement speed and agency on duration estimation of human motion. Participants were recorded using optical motion capture while they performed dance-like movements at three different speeds. They later returned for a perceptual experiment in which they watched point-light displays of themselves and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Faster tempo has been linked to higher felt emotional arousal (Droit-Volet et al, 2013 ), while music perceived high in arousal level has been associated with high expressiveness (Fernández-Sotos et al, 2016 ). The current study is further in line with Allingham et al’s ( 2021 ) research, as they have found an association between increases in movement speed and a rise in perceived expressiveness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Faster tempo has been linked to higher felt emotional arousal (Droit-Volet et al, 2013 ), while music perceived high in arousal level has been associated with high expressiveness (Fernández-Sotos et al, 2016 ). The current study is further in line with Allingham et al’s ( 2021 ) research, as they have found an association between increases in movement speed and a rise in perceived expressiveness.…”
Section: Discussionsupporting
confidence: 93%
“…The emotional expressiveness may also mediate how individuals perceive the passing of time in relation to the internal clock speed. Fast movements were perceived to be more expressive (Allingham et al, 2021 ), indicating that fast stimuli positively predicted the perceived expressiveness. This finding with visual movements is in line with auditory evidence where an association between tempo of the music and expressiveness was found (Fernández-Sotos et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the analysis of head motion and orientation, which is crucial as head movements have been associated with influencing temporal perception and varying based on arousal and valence states (Behnke et al, 2021 ). In fact, the speed and nature of head movements can affect the perception of simultaneity between sensory events (Sachgau et al, 2018 ; Allingham et al, 2020 ) and can lead to recalibration of time perception in a virtual reality context (Bansal et al, 2019 ). To capture these dynamics, we extracted features from the x, y , and z signals of the accelerometer data, segmented into 2-s epochs with a 50% overlap.…”
Section: Methodsmentioning
confidence: 99%
“…The distributed account is supported by findings that audition has an advantage over vision and other sensory modalities in terms of duration discrimination (Grondin et al, 2008), reproduction (Gamache & Grondin, 2010), and estimation (Kanai et al, 2011). However, it should be noted that the domination of audition in temporal processing does not apply to all cases, particularly with biological trajectories or movements (Allingham et al, 2020).…”
Section: Introductionmentioning
confidence: 95%